Food service management for senior high - Tan, Lawrence Li; de Guzman, Florentine Cabuyao (Anvil Publishing Inc., 2016)
Food service management equips the students with knowledge on: the food service industry, culinary skills and methods, the food and beverage service sequence, beverages and bar operation and restaurants service equipment. This book also includes insights from seasoned local and international industry.